2007
DOI: 10.1074/jbc.m702238200
|View full text |Cite
|
Sign up to set email alerts
|

FSCB, a Novel Protein Kinase A-phosphorylated Calcium-binding Protein, Is a CABYR-binding Partner Involved in Late Steps of Fibrous Sheath Biogenesis

Abstract: We report characterization of a novel testis-and sperm-specific protein, FSCB (fibrous sheath CABYR binding), that is expressed post-meiotically and localized in mouse sperm flagella. FSCB was identified as a binding partner of CABYR, a calcium-binding protein that is tyrosine-phosphorylated during capacitation. Orthologous genes of FSCB are present in other mammals, including rat and human, and conserved motifs in FSCB include PXXP, proline-rich and extensin-like regions. FSCB is phosphorylated by protein kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 57 publications
(56 reference statements)
0
43
1
2
Order By: Relevance
“…As the name suggests, FSCB binds directly to CABYR (Li et al, 2007), and research has shown that it is phosphorylated by PKA and that it binds to Ca 2+ , placing it firmly in the centre of sperm motility pathways (Liu et al, 2011;Zhang et al, 2016). In light of the findings of this research, FSCB would be a very promising candidate for future research, and with the speed and ease of the CRISPR-Cas9 system, it should not take too long to discover the function in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…As the name suggests, FSCB binds directly to CABYR (Li et al, 2007), and research has shown that it is phosphorylated by PKA and that it binds to Ca 2+ , placing it firmly in the centre of sperm motility pathways (Liu et al, 2011;Zhang et al, 2016). In light of the findings of this research, FSCB would be a very promising candidate for future research, and with the speed and ease of the CRISPR-Cas9 system, it should not take too long to discover the function in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Herein we describe findings that indicate FSCB is a novel protein expressed specifically on the surface of the fibrous sheath of the mouse spermatozoa principal piece (6). FSCB is a calcium-binding protein, which can be phosphorylated by PKA in vitro.…”
Section: Introductionmentioning
confidence: 94%
“…We reported previously that FSCB is phosphorylated in vitro by the PKA catalytic subunit, and that it possesses multiple phosphorylation sites (6). To further investigate whether FSCB is phosphorylated during spermatozoa capacitation, spermatozoa before and at 2 h after capacitation were lysed and analyzed by Western blotting.…”
Section: Serine/threonine and Tyrosine Phosphorylation Of Fscb Duringmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 30 of the 322 specific RNAs retained in sperm were not identified as proteins during proteomic analyses (reviewed in Amaral et al 2014), but have been identified in sperm by western blot or in situ hybridization. This is best exemplified by PRM1 and FSCB (Li et al 2007;Jodar and Oliva 2014). Of the RNAs that remain as sperm-specific yet protein-absent, approximately 20 % correspond to non-coding RNAs including pseudogenes, intronic elements and long non-coding RNAs.…”
Section: Spermatozoal Retained Rnasmentioning
confidence: 99%